Variability of Sea Surface Temperature and Sea Surface Salinity in the Ambon Bay and its Relation to ENSO/IOD and Monsoon - Corry Corvianawatie; Mutiara Rachmat Putri; Sri Yudawati Cahyarini; Willem Merpy Tatipatta (Indonesian Journal of Geospatial, 2014)
Sea Surface Temperature (SST) and Sea Surface Salinity (SSS) are the most important oceanographic parameter. In this research we study local oceanographic condition in the Ambon Bay (3o40'S and 128o10'E); the variability of SST and SSS due to climatic events El NiÃ±o Southern Oscillation (ENSO), Indonesian Ocean Dipole (IOD), and Monsoon. SST data used from Extended Reconstructed Sea Surface Temperature version 3b (ERSST v3b) and SSS data from Simple Ocean Data Assimilation (SODA 2.2.4). Oceanic Nino Index 3.4 (ONI 3.4) and Dipole Mode Index (DMI) datasets are used to identify the effect of ENSO/IOD on the SST and SSS in the Ambon Bay. We used monthly datasets in 2000-2008 periods. Monsoonal variation dominants in monthly mean time scale. The maximum SST is occurred during the Northwest Monsoon (i.e. in December) and the minimum SST is occurred during the Southeast Monsoon (i.e. in August). While the maximum SSS is occurred in July and minimum SSS is occurred in April. Statistical analysis results there is high correlation between SST and wind speed r=-0.842 (n=108, p<0.05), SSS and wind speed r=0.493 (p<0.05).  However, there is very small correlation between SST/SSS anomaly and ONI/DMI. Correlation coefficient of SST anomaly with DMI is r=-0.365 (n=108, p<0.05), and with ONI 3.4 is r=-0.071 (n=108, p>0.05). The correlation coefficient of SSS anomaly with DMI is r=0.112 (n=108, p>0.05), and with ONI 3.4 is r=0.191 (n=108, p<0.05). Based on these reviews summarized that in the seasonal variation of SST and SSS in the Ambon Bay is dominated by the monsoonal effect rather than the ENSO and IOD events.